TINDAKAN WANPRESTASI PEMBERIAN UPAH TERHADAP PEKERJA BANGUNAN (Studi Kasus di Jor. Aliran Sungai Nag. Taluk Kec. Lintau Buo Kab. Tanah Datar) - Resque Ilham Maulana; Elimartati Elimartati (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2023)
From the results of the study it was found that the implementation of the contract/agreement used in Jorong Sungai Nagari Taluk, Lintau Buo was a contract agreement carried out by the shop owner with the chief craftsman using a wholesale system (shirkah abdan) which was explained directly or verbally without the others. Between the chief mason and workers also uses a wholesale system (shirkah abdan) which is explained verbally/spokenly, but wages for construction workers are calculated daily as the custom for construction workers in Lintau Buo. In the contract/agreement that is carried out there is an agreement to give bonus wages if the work is completed before the due date where the number of working hours per day is not set because the workers try to get the job done quickly in the hope of getting a bonus. But in reality the bonus has not been clear until now. So that in giving wages there is an act of breaking promises or defaults on construction workers. Where construction workers feel disadvantaged because each member does not receive a wage bonus. Breach of promise in a contract is regulated in the Compilation of Sharia Economic Law article 36.